PENDIDIKAN ISLAM DAN ADAT ISTIADAT MELAYU: HUBUNGAN, NILAI, DAN TRANSFORMASI DI ERA MODERN - Rahmad Mahadi; Siska Wulandari; Ismail Sukardi; Nyayu Soraya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education has an important role in shaping the character, morality and spirituality of students through internalizing the values ​​of the Koran and Hadith. In Malay society, Islamic education develops in harmony with customs based on the principle of "adat bersendi syarak, syarak berndi Kitabullah." This research aims to examine the relationship between Islamic education and Malay customs, identify Malay traditional values ​​that strengthen Islamic education, and analyze the transformation of Islamic Religious Education (PAI) in the traditions of Malay society in the modern era. This research uses a literature study method with a descriptive qualitative approach through analysis of various relevant scientific literature sources. The research results show that Islamic education and Malay customs have a mutually reinforcing relationship and have developed organically since the arrival of Islam to the archipelago. Traditional values ​​such as mutual cooperation, respect for teachers, manners, deliberation, and traditional rituals have been proven to support the implementation of Islamic education both formally and informally. In the modern era, Islamic Religious Education is being transformed through curriculum updates, the use of digital technology, and the revitalization of traditional institutions to maintain its relevance to current developments without losing its Malay-Islamic identity. Thus, Islamic education serves not only as a medium for transferring knowledge but also as an instrument for preserving the cultural and Islamic identity of the Malay community.